2018
DOI: 10.1177/1526602818759339
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Thoracic Endovascular Aortic Repair for Acute Type B Dissection in Patients With Intractable Pain or Refractory Hypertension

Abstract: TEVAR for UATBAD with intractable pain/refractory hypertension is safe but offers no short-term outcome advantage when compared to UATBAD patients without these features receiving BMT. A significant improvement in aortic remodeling was identified after TEVAR. The potential long-term reintervention and aorta-related mortality benefits of this favorable remodeling have yet to be defined and randomized trials are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Procedures for repairing proximal aortic dissection have shown markedly improved survival rates in the acute phase. 14 Nevertheless, some of the distal intimal tears and false lumens persist without intervention, especially in the descending aorta 5 and abdominal aorta. 15 Most Stanford type A aortic dissections have a patent distal false lumen after open repair of the ascending aorta, with disease progression at a rate of 1 to 3.7 mm per year.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for repairing proximal aortic dissection have shown markedly improved survival rates in the acute phase. 14 Nevertheless, some of the distal intimal tears and false lumens persist without intervention, especially in the descending aorta 5 and abdominal aorta. 15 Most Stanford type A aortic dissections have a patent distal false lumen after open repair of the ascending aorta, with disease progression at a rate of 1 to 3.7 mm per year.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared uncomplicated acute type B aortic dissections (UATBAD) with intractable pain or refractory hypertension which are treated with TEVAR or best medical therapy. The study showed that TEVAR was safe but did not offer a better short term outcome than the patients who are taking best medical therapy [14]. In our study group there were 2 patients with complicated acute type B dissection and one patient with a chronic type B dissection who have unthrombosed false lumen with progressive enlargement of diameter.…”
Section: Discussionmentioning
confidence: 71%
“…RTAD is a complication with low incidence (2.5-8%) but high mortality rate (37.1-40%) after TEVAR. 3–5 Although some patients received successful thoracotomy, multiple organ dysfunction syndrome and death are prevalent in the postoperative period. 6…”
Section: Discussionmentioning
confidence: 99%